2023
DOI: 10.1039/d3sc01734f
|View full text |Cite
|
Sign up to set email alerts
|

Probing collective terahertz vibrations of a hydrogen-bonded water network at buried electrochemical interfaces

Abstract: The exceptional properties of liquid water such as thermodynamic, physical, and dielectric anomalies originate mostly from hydrogen-bond networks of water molecules. The structural and dynamic properties of the hydrogen-bond networks...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…12−14 The influence of the energy transfer to the SERS detection of water may also imply that SERS spectroscopy is more sensitive to THz collective responses of water than the high-frequency OH vibrations due to the slower energy dissipation in low-frequency modes; THz responses of water were indeed able to be detected under moderate potential applications on Au surfaces. 71 ■ CONCLUSIONS SERS spectra of interfacial water molecules were measured on electrochemically roughened Ag surfaces in the wide frequency range between 8 and 4000 cm −1 (0.24 and 120 THz), which covers both THz and mid-IR regions. For the OH stretching band in the mid-IR region, the contribution of hydration shells was dominated in the SERS spectra.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12−14 The influence of the energy transfer to the SERS detection of water may also imply that SERS spectroscopy is more sensitive to THz collective responses of water than the high-frequency OH vibrations due to the slower energy dissipation in low-frequency modes; THz responses of water were indeed able to be detected under moderate potential applications on Au surfaces. 71 ■ CONCLUSIONS SERS spectra of interfacial water molecules were measured on electrochemically roughened Ag surfaces in the wide frequency range between 8 and 4000 cm −1 (0.24 and 120 THz), which covers both THz and mid-IR regions. For the OH stretching band in the mid-IR region, the contribution of hydration shells was dominated in the SERS spectra.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…If the intermolecular energy transfer via HB networks is indeed an essential factor to determine the SERS insensitivity to liquid water, any method to break HB networks should be effective to make water molecules SERS-detectable. For example, when a large electrochemical potential relative to PZC is applied at electrochemical interfaces, orientational changes of water molecules are induced in the electrical double layer, resulting in the creation of HB defects at the interface. , Indeed, it has been reported that interfacial water molecules become detectable in SERS under very negative potential applications, where the so-called H-down configuration of water is formed. The influence of the energy transfer to the SERS detection of water may also imply that SERS spectroscopy is more sensitive to THz collective responses of water than the high-frequency OH vibrations due to the slower energy dissipation in low-frequency modes; THz responses of water were indeed able to be detected under moderate potential applications on Au surfaces …”
Section: Resultsmentioning
confidence: 99%